Adapting CRISPR/Cas9 System for Targeting Mitochondrial Genome - Hussain, Syed-Rehan A.; Yalvac, Mehmet E.; Khoo, Benedict; Eckardt, Sigrid; McLaughlin, K. John (Frontiers in Genetics, 2021)
Gene editing of the mitochondrial genome using CRISPR-Cas9 system is highly challenging mainly due to sub-efficient delivery of guide RNA and Cas9 enzyme complexes into mitochondria. In this study, we were able to perform gene editing in the mitochondrial DNA by appending NADH-ubiquinone oxidoreductase chain 4 (ND4) targeting guide RNA to a RNA transport derived stem loop element (RP-loop) and expressing the Cas9 enzyme with preceding mitochondrial localization sequence. Our results showed mitochondrial co-localization of RP-loop gRNA and a marked reduction of ND4 expression in the cells carrying a A11204G variant in their ND4 sequence coincidently decreasing the mtDNA levels. This proof-of-concept study suggests that stem loop element added sgRNA can be transported to the mitochondria and functionally interact with Cas9 to mediate sequence specific mtDNA cleavage. Using this novel approach to target the mtDNA, our results provide further evidence that CRISPR-Cas9 mediated gene editing might potentially be used to treat mtDNA related diseases.